2013
DOI: 10.1016/j.biombioe.2012.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Mapping energy crop cultivation and identifying motivational factors among Swedish farmers

Abstract: Based on a meta-study, the paper describes the existing options, areal extents, and Swedish farmers' conditions for energy crop production promoted by the governments to mitigate and adapt to climate change. The drivers of and barriers to cultivating various energy crops are described in terms of a variety of motivational factors. The approach used peer-reviewed and grey literature using three internet sources. Questions addressed include the energy crops available to Swedish farmers and how well established t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…This persistent chicken-and-egg situation, along with the risk aversion of the general farming community with respect to fundamental changes to their target market and their planting-growing-harvesting activities (see [18,62]), means it would be overly optimistic to assume idle land will be allocated toward the production of dedicated energy crops. For these reasons, production potentials are estimated with and without inputs from switchgrass production.…”
Section: Estimating Biomass From Grassland Plantationsmentioning
confidence: 99%
“…This persistent chicken-and-egg situation, along with the risk aversion of the general farming community with respect to fundamental changes to their target market and their planting-growing-harvesting activities (see [18,62]), means it would be overly optimistic to assume idle land will be allocated toward the production of dedicated energy crops. For these reasons, production potentials are estimated with and without inputs from switchgrass production.…”
Section: Estimating Biomass From Grassland Plantationsmentioning
confidence: 99%
“…The review indicated that, although economic incentives to change the production system are strong, factors such as values (e.g., aesthetics), knowledge (e.g., habits and knowledge of production methods), and legal conditions (e.g., property rights and cultivation licensing) may also be crucial for production system change [10]. However, no empirical, explorative study of this matter has yet been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The three most extensive energy crops currently produced in Sweden are straw (a by-product), oil crops, and wheat, each covering 15,000-25,000 ha [10]. Earlier studies of conditions for land use change at the Swedish and international levels have demonstrated the importance of economic incentives in encouraging individual actors to change production or land use [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations